VD_FINDINFO HC / 2014 / 395 vom 23. Mai 2014 - VD Tribunal cantonal (2014)
COMPÉTENCE INTERNATIONALE, COMPÉTENCE RATIONE LOCI, DÉCISION INCIDENTE | 308 al. 1 let. a CPC (CH), 308 al. 2 CPC (CH), 312 al. 1 CPC (CH)